The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/sym12020239
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Progress in Modification of Polymeric Membranes Using Organic Macromolecules for Water Treatment

Abstract: For decades, the water deficit has been a severe global issue. A reliable supply of water is needed to ensure sustainable economic development in population growth, industrialization and urbanization. To solve this major challenge, membrane-based water treatment technology has attracted a great deal of attention to produce clean drinking water from groundwater, seawater and brackish water. The emergence of nanotechnology in membrane science has opened new frontiers in the development of advanced polymeric memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 177 publications
0
11
0
Order By: Relevance
“…Another solution to overcome mechanical improprieties is the application of electrospun nanofiber as functionalized TFC membranes which have received significant attention in water disinfection ( Nagandran et al, 2020 ). Moreover, the intended incorporation of electrospun nanofiber with functional molecules provides a great possibility for designing a membrane with specific activities, especially incorporation with biocides results in the fabrication of a membrane with significant antibacterial or antiviral activities.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Another solution to overcome mechanical improprieties is the application of electrospun nanofiber as functionalized TFC membranes which have received significant attention in water disinfection ( Nagandran et al, 2020 ). Moreover, the intended incorporation of electrospun nanofiber with functional molecules provides a great possibility for designing a membrane with specific activities, especially incorporation with biocides results in the fabrication of a membrane with significant antibacterial or antiviral activities.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The hydration of hydrophilic brushes has been documented to provide an unfavorable atmosphere for the fixation of bacterial cells [ 51 ]. The grafting of hydrophilic, sulfonated anionic polymer brushes ruptures the outer membrane of bacteria, resulting in the damage of bacterial enzymes [ 66 , 67 ]. Therefore, it can be concluded that upon the hydration of grafted sulfonate, the PSPMK brush applies stress on the outer membrane surface, destroying the membrane, resulting in enzyme damage and protein denaturation ultimately causing the death of microbes [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this context, the contributions by Sapalidis on polyvinyl alcohol membranes [2], Duolikun et al on asymmetric cellulose membranes [3], Pulyalina et al on polyimide-based membranes [4,5], and Boussemghoune et al on ceramic membranes [6] are in line with the investigation of "old membrane materials," whilst the two papers by Nagandran et al [7] and Goh et al [8] focus on the enhancement of polymeric membrane performance by their modification by macromolecules and nanofillers, respectively.…”
mentioning
confidence: 77%